Involvement of microtubules in the link between cell volume and pH of acidic cellular compartments in rat and human hepatocytes. - Busch, G L (1994)
Cell swelling is shown to induce an increase in acridine orange fluorescence intensity, an effect pointing to the alkalinization of acidic vesicles. Since autophagic hepatic proteolysis is accomplished by pH-sensitive proteinases within acidic lysosomes, this effect may contribute to the well-known inhibitory effect of cell swelling on proteolysis. In the present study, the role of microtubules in volume-dependent alterations of pH in acidic vesicles of rat and human hepatocytes was studied. Colcemid and colchicine were used to depolymerize microtubules and vesicular pH was monitored using two different fluorescent dyes, fluorescein isothiocyanate conjugated-dextran and acridine orange. Colcemid and colchicine, but not the inactive stereoisomer gamma-lumicolchicine, blunted the increase of pH during osmotic cell swelling. The alkalinization of acidic vesicles by NH4Cl was not significantly modified by colcemid or colchicine, indicating that the vesicles were still sensitive to alkalinizing procedures other than cell swelling. Further, colchicine, but not gamma-lumicolchicine, inhibited the antiproteolytic action of osmotic cell swelling. The present observations point to an involvement of the microtubule network in the link of cell volume, lysosomal pH, and proteolysis.